Functional Brain Changes Due to Chronic Abdominal Pain in Inflammatory Bowel Disease: A Case-Control Magnetic Resonance Imaging Study. Issue 2 (19th February 2022) - Prüß, Magdalena S.; Bayer, Arian; Bayer, Kian-Elias; Schumann, Michael; Atreya, Raja; Mekle, Ralf; Fiebach, Jochen B.; Siegmund, Britta; Neeb, Lars
Abstract : INTRODUCTION: Various chronic pain conditions go along with functional and structural brain changes. This study aimed to investigate functional and structural brain changes by magnetic resonance imaging (MRI) in inflammatory bowel disease (IBD) patients with chronic abdominal pain. METHODS: Sixty-four subjects were included in the final analysis (32 IBD patients with chronic abdominal pain; 32 age-matched and sex-matched controls). All patients suffered from chronic abdominal pain, defined as a score of ≥3/10 on the visual analog scale for at least 3 months in the past 6 months. Besides structural MRI, resting state functional MRI was used to compare functional connectivity of 10 networks between groups. RESULTS: Patients with IBD showed no structural brain alterations but a significantly increased resting state functional connectivity of the secondary somatosensory cortex within the salience network. DISCUSSION: Because the secondary somatosensory cortex saves sensory stimuli and compares novel information with latter experiences, these functions may be maladaptive in IBD patients with abdominal pain.